[Discussion of The SEC's Influence on Accounting Standards: The Power of the Veto]: A Reply - Newman, D. Paul (Journal of Accounting Research, 1981)
D. Paul Newman, [Discussion of The SEC's Influence on Accounting Standards: The Power of the Veto]: A Reply, Journal of Accounting Research, Vol. 19, Studies on Standardization of Accounting Practices: An Assessment of Alternative Institutional Arrangements (1981), pp. 170-173